Ketahanan hidup 2 tahun pasien tuberkulosis resisten obat di RS. Moewardi Surakarta tahun 2010-2014 - Artika Fristi Firnawati; Riris Andono Ahmad; Heni Retnowulan (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Two year survival of drug resistant tuberculosis patients in Moewardi hospital in Surakarta in 2010-2014PurposeThe purpose of this study was to determine the two year survival rate and predictor factors of mortality in drug resistant tuberculosis patients during treatment at the Moewardi Hospital in Surakarta.MethodsThis research was a retrospective cohort study of 250 drug resistant tuberculosis patients receiving treatment in the Moewardi Hospital in January 2011-September 2014. Data were analyzed using survival analysis to find factors affecting the 2 year survival. Our variables were demographic factors, disease characteristics and treatment history. We used Cox regression test with 5% significance level.Results2-year survival rates of drug resistant patients was 74.82%. age, the type of patient, HIV status, side effects of medications and culture conversion were significant to survival rate in bivariate analysis. Cox regression test showed that aged ≥ 40 years (HR 3.221; 95% CI 1.037 to 10.001) and have HIV-positive status (HR 18.086; 95% CI 1.958 to 167.073) were related with reduction of two year survival rate in drug resistant tuberculosis patient. ConclusionAge above 40 years old and HIV positive status for drug-resistant tuberculosis patients may accelerate their death. The screening of HIV in drug resistant tuberculosis patients is needed in order to increase two year survival rate of patients during treatment.